Nineteen significant marker/trait combinations associated with eight grain quality traits valuable for selecting rice germplasm from Latin America and the Caribbean - CGIAR Research Program on Rice (2021)
Markers are being validated in elite breeding lines from CIAT/FLAR. Data is already available from about 1500 F5 lines and a second phase of validation is on going.